Pembuatan Arang Aktif Kultur Jaringan dari Pelepah Kelapa Sawit (Elaeis guineensis Jacq.) dengan Metode Aktivasi Fisika-Kimia - Yudia Azmi; Eka Sri Utami; Reiza Mutia AR (JURNAL PERTANIAN, 2026)
Oil palm frond has potential to be utilized as activated charcoal for plant tissue culture as phenolic compound absorber which causes browning and to promote explant growth. The objectives of this study were to produce activated charcoal from palm oil fronds which has characteristics in accordance with Indonesian National Standards (SNI 06-3730-1995) and commercial activated charcoal for plant tissue culture, to obtain larger activated charcoal pores and clean from the impurities, and to find optimum activated temperature in producing oil palm frond’s activated charcoal using physical-chemical activation method. The research design used was a non actorial - completely randomized design consisted of 4 treatments and 3 replications, namely E0 (control, without physical activation), E1 (physical activation of 450 °C), E2 (physical activation of 600 °C), E3 (physical activation of 750 °C). The parameters observed were the yield of activated charcoal (%), moisture content (%), ash content (%), iodine absorption (mg/g), volatile matter (%) and surface morphology of activated charcoal. The yield of activated charcoal ranged from 0.56 to 1.09%. All treatments significantly affected moisture content, ash content, iodine adsorption, and volatile matter. Overall, the characteristics of the activated charcoal met the SNI standards and commercial tissue-culture charcoal, except for moisture content. The 750 °C activation temperature (E3) was identified as the optimum condition, producing low moisture and ash content, high iodine adsorption, low volatile matter, and larger, cleaner pore morphology